Rates, types and associations of sexual risk behaviours and sexually transmitted infections in those with severe mental illness: a scoping review. (August 2020) - Stevens, Meg; Ratheesh, Aswin; Watson, Amity; Filia, Kate; Donoghue, Brian O; Cotton, Sue M.
Highlights: Sexual health is an important aspect of physical health to consider in those with severe mental illness Individuals with severe mental illness are more likely to display an array of sexual risk behaviours including inconsistent condom use, multiple sexual partners, and transactional sexual acts As a result of sexual risk behaviours, those with severe mental illness are at more risk of sexually-transmitted infections and human immunodeficiency virus Abstract: The aim of this scoping review was to: (i) determine rates and types of sexual risk behaviours and sexually-transmitted infections (STIs) in those with severe mental illness (SMI); and (ii) delineate correlates of poor sexual health outcome. The online databases OVID MedLine and PsycINFO were searched from databases inception to February 2018 for any literature with a focus on sexual risk behaviours (inconsistent condom use, multiple sexual partners, substance use and transactional sexual acts) or STIs in SMI populations. Fourteen studies were identified; the quality of these studies ranged from poor to moderate. Outcome definitions were heterogeneous, precluding meta-analysis. We found rates of sexual risk behaviours and STIs to be more common among those with SMI than the rates in the general Australian population. Current studies do not acknowledge the relationship of sexual risk behaviours and STI risk and hence do not provide a full model of sexual health outcomes in those with SMI. In order to improve sexual health outcomes in SMI populations, further research is required of greater methodological rigor, with consensus in the definition of sexual risk behaviours, clarifying causal relationships and where in the course of SMI that these outcomes emerge.